DEX‐2‐TKA ‐ DEXamethasone twice for pain treatment after Total Knee Arthroplasty: Detailed statistical analysis plan for a randomized, blinded, three‐group multicentre clinical trial. Issue 6 (3rd March 2020) - Gasbjerg, Kasper S.; Hägi‐Pedersen, Daniel; Lunn, Troels H.; Overgaard, Søren; Pedersen, Niels Anker; Bagger, Jens; Lindholm, Peter; Brorson, Stig; Schrøder, Henrik M.; Thybo, Kasper H.; Mathiesen, Ole; Jakobsen, Janus C.
Abstract : Background: Optimization of post‐operative pain treatment is of upmost importance. Multimodal analgesia is the main post‐operative pain treatment principle, but the evidence on optimal analgesic combinations is unclear. With the "DEXamethasone twice for pain treatment after TKA" trial, we aim to investigate the role of one or two doses of glucocorticoid for post‐operative pain treatment after total knee arthroplasty. To ensure transparency and minimization of bias, we present this article with a detailed statistical analysis plan, to be published before the last participant is enrolled. Methods: "DEXamethasone twice for pain treatment after TKA" (DEX‐2‐TKA) is a randomized, blinded, three‐group multicentre clinical trial. Participants will be randomized to one of three intervention groups: single dose of iv dexamethasone 24 mg, two consecutive doses of iv dexamethasone 24 mg or matching iv placebo. All three intervention groups will receive paracetamol, NSAID (ibuprofen) and local infiltration analgesia. Participants, treatment providers, outcome assessors, data managers, statisticians and conclusion drawers will be blinded to the allocated intervention. The primary outcome is total opioid consumption (iv morphine milligram equivalents) 0‐48 hours post‐operatively. Secondary outcomes are (1) visual analogue scale pain levels: (a) during active 45 degrees flexion of the knee at 24 and 48 hours post‐operatively, (b) at rest at 24 and 48 hours post‐operatively, and (c) during 0‐24 hours (highest score) and 24‐48 hours post‐operatively (highest score); and (2) the proportion of participants with one or more adverse events within 48 hours post‐operatively. Discussion: The DEX‐2‐TKA trial will provide high quality data regarding benefits and harms of adding one or two high‐doses of dexamethasone to a multimodal analgesic regimen. Trial registration: EudraCT: 2018‐001099‐39 (08/06‐18); ClinicalTrials.gov: NCT03506789 (24/04‐2019).